Parental and Peer Violence, Self-Esteem, Self-Control, and Aggressive Adolescent Behavior - Dafina Zulfarin; Dwi Hastuti; Diah Krisnatuti (Indonesian Journal of Multidisciplinary Science, 2023)
Aggressiveness behavior is an act of a person that aims to harm and harm others both verbally and physically. The main objective of this study was to analyze the influence of violence perpetrated by parents and peers, self-esteem, and self-control on aggressiveness behavior. This study used a cross-sectional study design with non-probability sampling and voluntary sampling techniques on 120 Vocational School adolescents who have intact families and live together in Bogor City. The data collection uses survey techniques. This study was analyzed using a structural equation model. The results of the study revealed that violence committed by parents and peers has a significant positive direct and indirect influence on the aggressiveness behavior of adolescents. Meanwhile, self-esteem and self-control have a significant negative direct influence on the behavior of aggressiveness. It is hoped that parents and the school can become role models for adolescents and can work together in educating children positively. Online promotion using influencers related to positive parenting needs to be done.